Replacement of Coarse Aggregate with Marble Waste for The Preparation of Alkali Activated Concrete - K. Srinivasa Rao, Rakesh Reddy Erri, U. Madhu, Prasanna Kumar Bethu, Srivallika (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Concrete is the most widely used man-made construction material from ages due to its versatility and cost effectiveness. Ordinary Portland Cement (OPC) has been conventionally used as the primary binder to produce concrete. One ton production of Portland cement emits approximately about 0.8 to 1 ton of carbon dioxide into the atmosphere, including for burning of the fuel fossils and for process of production using raw materials. This enormous liberation of carbon dioxide from the cement industries is one of the major issues for the cause of ecological imbalance, resulting in greenhouse effect. Hence several efforts have been in progress to reduce the global warming issue. To reduce these carbon dioxide emissions, one of the possible alternatives is the use of alkali activated binders using industrial by-products containing alumino-silicate materials such as Ground Granulated Blast furnace Slag (GGBS), fly ash etc. GGBS is obtained from a blast furnace in water or steam by quenching molten iron slag (a by-product of iron and steel-making), to produce a glassy, granular product which is then dried and ground into a fine powder. Fly-ash & GGBS is considered as a sole binder in the production of Alkali Activated Concrete (AAC) by activating with sodium hydroxide and sodium silicate solutions. The present project work, the molarity of sodium hydroxide 10M and 60% Fly-ash and 40%GGBS as cementitious material (cement replacement) with various percentages of coarse aggregate replacing with marble waste i.e. 10%, 20%, 30% 40% and 50%. A comparative study was conducted on the performance of mechanical properties of oven (600C) and ambient cured (7, 28 days) marble waste-based alkali activated concrete. It was observed that higher compressive strength (28 days ambient curing) was attained for the eco-friendly concrete (AAC) up to 30% replacement of coarse aggregate with marble waste.